Case Report: Hemodynamic Instability Caused by Splenic Rupture During Video-Assisted Thoracoscopic Lobectomy - Liu, Chun-tong; Wu, Ting-ting; Ding, Yun-ying; Lin, Jin-long; Zhou, Shuang; Liu, Hong; Ji, Fu-hai; Peng, Ke (Frontiers in Surgery, 2022)
Background: Video-assisted thoracoscopic surgery (VATS) has been widely performed for patients with lung cancer. Splenic rupture after VATS lung procedures is a very rare and serious event. Case Presentation: We reported a case with hemodynamic instability after left lower VATS lobectomy. There was no evidence of diaphragmatic injury during the surgery. Computed tomography (CT) showed spleen injury and large amount of fluid in the abdominal cavity. Emergent laparotomy was performed, and splenic rupture was diagnosed. The patient underwent splenectomy, with two lacerations at the diaphragmatic surface of the spleen. The patient did well postoperatively and was discharged from the hospital on postoperative day 5. Conclusion: There are few similar cases reported in the literature. Persistent hemodynamic instability due to the rupture of spleen is life-threatening. In the situation of unexplained hypotension during VATS procedures (especially left-sided approaches), the possibility of splenic injury and rupture should be considered. Abdominal ultrasonography and/or CT examinations should be carried out for prompt diagnosis and treatment of such rare complication.